Reliability of Spatiotemporal Characteristics During Single-Legged Hop and Bilateral Drop Jump Tasks Using an Instrumented Pressure Walkway - Matthew McManigal; Austin Post; Michael Allen; Alyx Jorgensen; MIke Rosenthal; Michael Wellsandt; Matthew Tao; Elizabeth Wellsandt (International Journal of Sports Physical Therapy)
# Background